Educação Física escolar em tempos de pandemia: as aulas remotas no IFAM Parintins-AM - Cavalcante, Amanda Lívia Belém (Brasil, 2022)
This work aims to analyze the planning and performance of Physical Education teachers at IFAM, Campus Parintins-AM, regarding learning and challenges during remote teaching in the year 2021. It is a case study with a qualitative approach, it was carried out at the Federal Institute of Education, Science and Technology of Amazonas, Parintins campus, whose subjects were 2 (two) teachers who teach Physical Education classes at that institution. For data collection, a semi-structured questionnaire was used, sent to teachers by WhatsApp individually. The results obtained are that they were forced to adapt their lesson plans, use strategies and get used to the reality of remote teaching, which caused great challenges, but brought learning. The challenges were numerous, including the planning of remote classes, teaching classes virtually, internet access, lack of materials, precarious connection signal. All the aforementioned factors made it difficult for the teaching work to carry out a good class, as well as to plan and teach remotely, needing to use the best possible strategies for it to be carried out. There were also positive points, associated with facing this challenge, learning, autonomy demand greater infrastructure conditions, use of technology, exploring the digital world, participation in courses and scientific events served as learning for teachers. The need for improvement in this area is important, as it prepares them to work in remote teaching. The challenges that the COVID-19 pandemic brought to the educational space are notorious, but technology has become a great ally of pedagogical practice. This new understanding of remote teaching was challenging and led teachers to seek new learning to respond to this new scenario.